DeterminationofQualityofLifeforAdultPatients with Limbs Loss - Hussein H. Atiyal (Iraqi National Journal of Nursing Specialties, 2023)
ObjectivGThesfudyainedtodeterminequa"tyoflifedomainsforadultpatientswithlimbslossandtoidentify thea§sociationbetweenqualityoflifedomainsanddemographiccharacteristicsandmedicalinformation. Metliodology: A descriptive study was carried out at Baghdad artificial limb center, AI-Salam medical rehabilitation center, AI-Ghadeer medical rehabilitation center and the rheumatoid and medical rehabilitation center for the period from September 2007 to April 2008. A purposive "non- probabilfty’ sample of (200) patientswithlimbsloss.Questionnaireformwasconstructedforthepurposeofthestudy.Datawerecollected throughtheap|ilicationofthequestiormaireandinterviewtechnique.Dafawereanalyzedthroughdescriptive statisticalapproach(frequency,percentageandmeanofscore)andinferentialstatisticalapproach(chi-square, standard deviation and correlation coefficient). Results:Thefindingsofthesfudyhaverevealedtliatmo§tofpatientswithlimblossarewithmeanage(46.15) years, mostly males, living in urban residence, manied, living in nuclear family and prinay school graduate withI.etiredoccupation,butinsufficientmonthlyincomeinspiteoflivinginownedhouse.Mostofthepatients withlimblosshavechangedtheirjobsandreducedthehoursofworking.Mostofthemhavelosttheirlimbsfor (I- 5) years with unilateral lower limb and below-knee; walking with crutches and the trauma was the most common cause of linb loss. However, most of them visit rchabilhation centers and get benefits from rehabilitation. Recommendations: The study recommended tha. educational program for liewly limb loss for physiotherapy and occupational therapy and further studies can be conducted on large sample size about adaptation of the patients with limbs loss.